Bacteriocins to control Campylobacter spp. in poultry--A review - Svetoch, E.A; Stern, N.J (Poultry science, 2010)
The unacceptably high frequency of Campylobacter jejuni transmission from poultry to humans encourages scientists to consider and create alternative intervention strategies to control the pathogen in poultry production. Extremely high numbers of Campylobacter (often >10⁸ cfu/g of poultry intestinal material) potentiate high numbers of the organism on the processed broiler carcass with increasing consequent human health risk. Many scientists believe interventions during poultry production portend the greatest opportunity for reducing risk of disease. Over the past 10 yr, we have focused our studies on nonantibiotic bacteriocin application to intervene during animal production and this is the subject of the current review. The application of therapeutic bacteriocin treatments to reduce poultry colonization diminishes Campylobacter from >10⁸ cfu/g of cecal materials to nondetectable or very low levels in treated birds. Further, the review provides scientists with a useful starting point for the further development of industry-applicable interventions leading to reduced transmission of this agent in human disease.